Evaluasi penerapan sanitasi pada proses pengolahan produk manisan salak pondoh di UMKM Sarisa Merapi Sleman, Yogyakarta - Wahyu Triariyani; Ibdal Ibdal; Rini Handayani (UPT Percetakan dan Penerbitan Universitas Jember, 2022)
Sarisa Merapi is a micro, small and medium enterprise (MSME) engaged in food processing such as candied snakefruit, snakefruit's juice, snakefruit's lunkhead, telang tea, and eggroll. Among these products, candied snakefruit is the most demanded product due to its sweet and fresh taste, and cheap. The purpose of the study was to evaluate the production process, sanitation application, and quality control of candied snakefruit products in Sarisa Merapi. Data were collected through observation, interviews, literature study and documentation focused on preparing raw materials, processing and packaging. The production process of candied snakefruit includes sorting, stripping, cutting, soaking, washing, draining, boiling, draining, and packaging and storage. The observations found that the application of sanitation and hygiene in the production of candied snakefruit is quite good. However, some problems such as the condition of walls and floors were difficult to clean, workers did not routinely use aprons, and the production room did not have wall partitions to separate the spaces. These problems need to be addressed to minimize the negative impact on the products produced and also on consumers.